IMPLEMENTASI ALGORITMA BYTE PAIR ENCODING UNTUK KOMPRESI FILE - Ahmad Meidy Ruslida; Sapri Sapri; Devi Sartika (Jurnal Media Infotama, 2022)
ABSTRACT Data compression is a field that focuses on forming a small output file from a large file. The need for compression has given birth to several methods that can be implemented in communication activities on the network as well as on storage activities. The byte pair encoding algorithm is a compression algorithm that takes advantage of the emergence of repeated or frequent character byte pairs. The repeating character byte pairs are in the data and are substituted with a wildcard byte where the wildcard byte is not in the character byte series of the file. One of the well-known compression methods is the byte pair encoding compression method. The implementation of the system uses the Visual Basic 2010 programming language and the method used in this research is an applied research method. Keywords: Compression, Byte Pair Encoding, Document.